How we teach science what's changed, and why it matters - Rudolph, John L., 1964- (Harvard University Press, 2019)
The science taught in high schools-Newton's theory of universal gravitation, basic structure of the atom, cell division, DNA replication-is accepted as the way nature works. What is puzzling is how this precisely specified knowledge could come from an intellectual process-the scientific method-that has been incredibly difficult to describe or characterize with any precision. Philosophers, sociologists, and scientists have weighed in on how science operates without arriving at any consensus. Despite this confusion, the scientific method has been one of the highest priorities of science teaching in the United States over the past 150 years. Everyone agrees that high school students and the public more generally should understand the process of science, if only we could determine exactly what it is. From the rise of the laboratory method in the late nineteenth century, through the "five step" method, to the present day, John Rudolph tracks the changing attitudes, methods, and impacts of science education. Of particular interest is the interplay between various stakeholders: students, school systems, government bodies, the professional science community, and broader culture itself. Rudolph demonstrates specifically how the changing depictions of the processes of science have been bent to different social purposes in various historical periods. In some eras, learning about the process of science was thought to contribute to the intellectual and moral improvement of the individual, while in others it was seen as a way to minimize public involvement (or interference) in institutional science. Rudolph ultimately shows that how we teach the methodologies of science matters a great deal, especially in our current era, where the legitimacy of science is increasingly under attack.--